Uncomfortable truths – teamworking under lean in the UK. Issue 3 (4th February 2017) - Carter, Bob; Danford, Andrew; Howcroft, Debra; Richardson, Helen; Smith, Andrew; Taylor, Phil
Abstract: A recent contribution in this journal – Procter, S. and Radnor, Z. (2014) 'Teamworking under Lean in UK public services: lean teams and team targets in Her Majesty's Revenue and Customs (HMRC)' International Journal of Human Resource Management, 25:21, 2978–2995 – provides an account of teamworking in the UK Civil Service, specifically Her Majesty's Revenue and Customs (HMRC), focused on the relationship between recently implemented lean work organisation and teams and teamworking. Procter and Radnor claim in this work that it delivers a 'more nuanced' analysis of lean in this government department and, it follows, of the lean phenomenon more generally. Our riposte critiques their article on several grounds. It suffers from problems of logic and construction, conceptual confusion and definitional imprecision. Methodological difficulties and inconsistent evidence contribute additionally to analytical weakness. Included in our response are empirical findings on teamworking at HMRC that challenge Procter and Radnor's evidential basis and further reveal the shortcomings of their interpretation.